2012
DOI: 10.4315/0362-028x.jfp-12-229
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide Content Distribution and Possible Alternative Ingredients for Snack Foods

Abstract: Acrylamide (AA) contents in 294 snack foods including cereal-based, root- and tuber-based, and seafood-based foods, nuts, dried beans, and dried fruits purchased in Taiwan were determined by gas chromatography-mass spectrometry in this study. The highest levels of average AA content were found in root- and tuber-based snack foods (435 μg/kg), followed by cereal-based snack foods (299 μg/kg). Rice flour-based, seafood-based, and dried fruit snack foods had the lowest average AA content (<50 μg/kg). This is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
3
8
1
Order By: Relevance
“…In 2006, Spain has reported an average for corn based cereals to be 207 μg/kg which is comparable to our study [ 20 ]; however more recently Mesias have shown that the mean acrylamide content for corn based cereals in Spain was significantly lower at 64 μg/kg [ 21 ]. Among the Taiwanese population, Cheng reported the mean acrylamide intake from corn based cereal at 271 μg/kg, a result which is comparable to that shown in this study [ 22 ].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In 2006, Spain has reported an average for corn based cereals to be 207 μg/kg which is comparable to our study [ 20 ]; however more recently Mesias have shown that the mean acrylamide content for corn based cereals in Spain was significantly lower at 64 μg/kg [ 21 ]. Among the Taiwanese population, Cheng reported the mean acrylamide intake from corn based cereal at 271 μg/kg, a result which is comparable to that shown in this study [ 22 ].…”
Section: Resultssupporting
confidence: 86%
“…The average concentration of acrylamide at the 95% confidence level was found to range between 161.05 μg/kg and 350.83 μg/kg (t-statistic). Our values are lower than those reported in Spain where an average of 382 μg/kg was detected [20], while in Taiwan the average was found to be 305 μg/kg [22].…”
Section: Acrylamide Analysiscontrasting
confidence: 96%
“…These results may be explained by the presence of acrylamide precursors in these cereals, which together with other ingredients in the recipe and the extent of the processing conditions applied contribute to the generation of process contaminants. 18,19 Asparagine and reducing sugars are the main precursors for acrylamide formation in food matrices and in cerealderived products the critical factor is the free asparagine content. 20 The protein content and amino acid composition differ within cereal varieties and, therefore, in the absence of other ingredients, the type of cereal used in the formulation of biscuits will influence drastically the acrylamide formation.…”
Section: Acrylamide Levels In Biscuits: the Effect Of Type Of Cereal mentioning
confidence: 99%
“…Acrylamide is formed during thermal treatments applied in the snack industry, such as frying, extrusion or baking . This compound is produced as the result of the reaction between asparagine and reducing sugars as main precursors and has been identified as a public health concern due to its relation with different types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1 Acrylamide is formed during thermal treatments applied in the snack industry, such as frying, extrusion or baking. 2 This compound is produced as the result of the reaction between asparagine and reducing sugars as main precursors 3 and has been identified as a public health concern due to its relation with different types of cancer. The European Food Safety Authority (EFSA) has worked for many years on the elaboration of different reports to make the food industry aware about the need of controlling the dietary acrylamide exposure.…”
Section: Introductionmentioning
confidence: 99%